Determinasi Tax Avoidance Melalui Capital Intensity, Sales Growth, Leverage dan Komite Audit - Rilis Anisatun Nasriyah; Ahmad Hijri Alfian (Politeknik Raflesia Press, 2026)
This study uses a quantitative approach using secondary data from the annual reports of manufacturing companies listed on the Indonesia Stock Exchange (IDX) for the 2021–2023 period, with 180 samples selected through a purposive sampling technique. The analysis was conducted using multiple linear regression with SPSS version 26. The results indicate that capital intensity has a negative and significant effect on tax avoidance; sales growth and leverage have a positive and significant effect; and the audit committee has a negative but insignificant effect.